Bibliometric Analysis of Philosophical Dimensions in Sport Based on Scopus Data - Triansyah, Andika; Kurniawati, Ani; Carsiwan, Carsiwan (Belantika Pendidikan, 2024)
This study aims to explore the literature on the dimensions of philosophy and sports based on scopus indexed articles. The research method used to conduct the analysis is bibliometric. Search and filtering strategy using PRISMA flow chart. The research review uses data in comma-separated values (CSV) format, which is then exported to Microsoft Excel and to visualize the search results of bibliometric analysis the tool used is VOSviewer. The conclusion of the study resulted in the development of publications with the domain of philosophy and sports dimensions experiencing fluctuating conditions, but in the last 10 years the number of publications has tended to be stable.